(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2007)
Neste artigo são confrontadas as idéias da cultura digital - ou cibercultura - e o plano real que são vividas no acesso aos documentos digitais. Palabras-chave: Cibercultura; Acesso universal. Abstract In this article the ideas of the digital culture - or cyberculture - are confronted and the real plane that are lived in the access to digital documents. Keywords: Cyberculture; Universal access Resumen En este artículo se confrontan las ideas de la cultura digital - o cibercultura - y el plano real que se vive en el acceso a los documentos digitales. Palabras clave: Cibercultura; Acceso universal.